Pendampingan Kegiatan Keagamaan Untuk Membentuk Karakter Religius Pada Siswa SMK di Wilayah Pesisir - Johara Indrawati (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2025)
The objective of this Community Service (PkM) activity is to mentor religious activities aimed at shaping the religious character of students at Arjasa Kangean Vocational High School (SMK), Sumenep Regency, located in the coastal area. The background of this activity is the existing character crisis in education and the urgent need to instill religious values through consistent habituation, considering that SMK Arjasa had never organized religious activities since its establishment in 2017. The implementation method was carried out through three stages: observation, execution, and evaluation, spanning from January 2 to January 25, 2024. The mentoring activities included routine congregational Dhuhr prayers, regular Islamic studies, and the provision of social assistance to the underprivileged community. The results of the PkM show a positive impact on the students, namely increased discipline and obedience in performing prayers, acquisition of new religious knowledge, and the growth of caring and mutual help attitudes towards the surrounding environment through social service activities. This mentoring program is recommended for continuation so that the students' religious character is sustainably embedded.